Absorption and Xylem Transport of 33P-Labeled Phosphorus in Nodulated Soybean Plants - Yoshiaki Yamamura; Seiya Nara; Kyoko Higuchi; Akihiro Saito; Takuji Ohyama (Agriculture, 2024)
Phosphorus (P) is an essential macro-element for plants, and understanding the characteristics of the absorption and transport of P in crops is essential. The low availability of P restricts the growth, nitrogen fixation, and yield of soybean plants. In this research, the radioisotope 33P was supplied to the culture solution to trace the absorption and transport of P in nodulated soybean plants monitored using an imaging plate. The absorption rate of 33P was almost the same under the light and dark conditions. The absorption rate of 33P in the decapitated roots was near to that of the intact plants under light. These results indicate that the P absorption is not affected by evapotranspiration over a short time period. Conversely, the 33P transport from the roots to the shoot was significantly lower under dark conditions than it was under light conditions, although some 33P reached the top of the shoots under both the light and dark conditions. The transport of P to the shoots depends on the transpiration supplemented by the root pressure. The multiplication value of the 33P concentration in the xylem sap and transpiration rate was almost equivalent to the transport rate of 33P in the intact shoots. This value may be adaptable and used to estimate the transport rate of P for the diagnosis.